Factors Determining City Brand Equity—A Systematic Literature Review - Hanna Górska-Warsewicz (Sustainability, 2020)
The aim of this study is to analyze factors determining city brand equity (CBE) on the bases of a systematic literature review (SLR) according to a procedure developed by Tranfield. Five databases were searched (Scopus, Web of Sciences, Google Scholar, EBSCO, and Elsevier) for studies containing the term ‘city brand equity’. In addition, databases were searched for ‘destination brand equity’ and ‘place brand equity’ statements focusing on city brands. This SLR contains 36 empirical studies and does not include conference materials, and books. The analysis was based on three issues: general information (author/authors, year of publication, research tools, sample size, city and country as well as sample population), research specification (variables, hypotheses or research questions, statistical methods and research tools), and findings related to CBE and practical implications for destination marketing organizations, and destination or city managers. In summary, there are many factors determining CBE, including brand image, brand quality and brand awareness. These factors are related to cultural, environmental and ecological elements, as well as infrastructure and services offered to tourists. Brand assets related to the perception of the city brands in various aspects also proved to be important.